Asthma self-management app for Indonesian asthmatics: A patient-centered design. (November 2021) - Ghozali, MT; Satibi, Satibi; Ikawati, Zullies; Lazuardi, Lutfan
Abstract: Background: A proper education on asthma self-management helps asthmatics to improve health outcomes, such as better asthma knowledge and self-efficacy, increased frequency of symptom-free days, reduced unscheduled healthcare visits and absence from school or work days. In this modern digital era, the use of smartphone apps is increasing rapidly and reaching almost all aspects of our life, including health promotion and patient education on asthma self-management. Studies found that the apps make it easier for asthmatics to receive the education. Objective: The aim of this study was to describe the systematic design, development, and implementation process of a Google Android OS asthma self-management smartphone app according to the Patient-Centered Design approach. Methods: The design, development, and implementation process of the app adopted the Patient-Centered Design approach, including: (1) user needs assessment, (2) design of the app prototype, (3) development of the app prototype, (4) usability test, and (5) product launch. For better results, the study involved end-users (asthmatics and health professionals) during the development of the app. Results: The study resulted in a Google Android OS asthma self-management app, namely AsmaDroid. The app was developed to feature 8 contents and functions, namely: asthma education, a list of asthma medications, asthma diary or journal, peak flow record, asthma control test, asthma action plan, a chat box, and a map of nearest local hospitals or health centers. It was also found that the average success rate of the app was as follow: "completed with ease" was 88.15%, "completed with difficulty" was 7.78%, and "failed to complete" was 4.07%. It means that the success rate of app was "very high". Conclusion: The implementation of Patient-Centered Design approach has been successfully completed for the development of AsmaDroid. However, additional research into the use of the app in the actual clinical world is highly required to demonstrate its effectiveness in improving the level of asthma knowledge, the quality of asthma control, and other health outcomes.